Оцінка вібростійкості моторно-трансмісійної установки тракторного самохідного шасі - Подригало, Михайло Абович; Подригало, Надiя Михайлівна; Аврунін, Григорій Аврамович (Національний технічний університет "Харківський політехнічний інститут", 2025)
В результаті проведеного дослідження отримано аналітичні вирази, що дозволяють провести оцінку вібростійкості моторно-трансмісійної установки тракторного самохідного шасі. Отримана математична модель дозволила також провести порівняльний аналіз вібростійкості моторно трансмісійної установки, ДВЗ яких мають два та три циліндри. Визначено також вилив кругової податливості грунта на величину мінімально допустимої середньої кутової швидкості ДВЗ. The ratio between the circular frequency of the internal combustion engine torque and the frequency of free oscillations of the system "engine-transmission-driving wheels-soil-translationally moving mass of the tractor" affects the vibration resistance of the motor-transmission unit of the tractor self-propelled chassis. Its low value leads to deterioration in the dynamic properties of the machine and the energy efficiency of technological operations. As a result of the study, analytical expressions were obtained that allow an assessment of the vibration resistance of the motor-transmission unit of the tractor self-propelled chassis. The obtained mathematical model also allowed a comparative analysis of the vibration resistance of the motor-transmission unit with internal combustion engine that have two and three cylinders. The effect of the circular compliance of the soil on the value of the minimum permissible average angular velocity of the internal combustion engine was also determined. Installing a three-cylinder internal combustion engine instead of a two-cylinder allows an increase in the vibration resistance of the motor-transmission unit of the tractor self-propelled chassis.
Evaluation of the vibration resistance of the motortransmission installation of the tractor self-propelled chassis
Keywords: вібростійкість; моторно-трансмісійна установка; тракторне самохідне шасі; vibration resistance; motor-transmission unit; tractor self-propelled chassis